The Origin, Physicochemical Properties, and Removal Technology of Metallic Porphyrins from Crude Oils - Jumina Jumina; Yehezkiel Steven Kurniawan; Dwi Siswanta; Bambang Purwono; Abdul Karim Zulkarnain; Agustinus Winarno; Joko Waluyo; Johan Syafri Mahathir Ahmad (Universitas Gadjah Mada, 2021)
Crude oil is an indispensable energy feedstock for daily activities, although some amounts of metallic porphyrins components with undesired characteristics have been identified. These constituents are assumed to originate from the geochemical process of chlorophyll and heme derivatives. In addition, their chemical structures have been thoroughly characterized using spectroscopy techniques, while several analytical methods were adopted in the detection and concentration quantification in the crude oils. The metallic porphyrins have several demerits, including the deactivation of used catalysts, contamination of the treated petrochemical products, and corrosion of the industrial equipment. Also, the removal process is considered challenging due to the strong interaction with the asphaltene fraction of crude oil. This review article, therefore, provides brief information on the origin, physicochemical properties, and possible removal technology of metallic porphyrins from crude oil samples. Besides, a better understanding of chemistry contributes a useful insight towards the development and establishment of better futuristic processing technology.